THE TAXONOMY OF FORESTRY TERMS IN THE MODERN UKRAINIAN LANGUAGE - Oksana Hrydzhuk (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2019)
The subject of the research is the analysis of forestry vocabulary. The purpose is to promote the enhancement taxonomy of forestry vocabulary in the modern Ukrainian language. For the analysis of the forestry vocabulary, we used such methods as scientific sources investigation, a descriptive method, methods of comparison, analysis and synthesis, as well as methods of classification and systematisation. Forestry vocabulary provided in the article includes terms, professionalisms, terminologised common lexical units and nomenclature nominations. We have revealed that forestry terminology contains general scientific terms, interdisciplinary terms and specific forestry terms. Terminological lexical units are understandable to everyone, but these lexemes are the obligatory component of the forestry terminological system, without them its integrity will be broken. We suggest paying special attention to the use of professionalisms that is caused by the peculiarities of the specialistsˊ activities and is associated with the use of a significant number of dialect names. Nomenclature names are used to designate as follows: wood species, types of cutting, means of the direct extinguishing of forest fires. Latin names of flora and fauna and taxonomic names are also considered to be the nomenclature names. The research has shown that these classes of nominative units (terms, professionalisms and dialect names) are applied simultaneously in forestry terminology. The need for proper knowledge of the terms and rules of their combination justifies the students' expediency to study the peculiarities of forestry vocabulary taxonomy. Mastering of terms will help students avoid mistakes in their speech, and improve the quality of future specialists' professional speech and also the level of terminological knowledge in general. The theoretical material developed is supposed to become the basis for practical classes and will be presented in future academic research in the didactic aspect.